To study the contribution of different geometric parameters on the failure load for multi holes pin joints prepared from glass/epoxy nanoclay laminates. (March 2018) - Singh, Manjeet; Saini, JS; Bhunia, H
The present work aims to analyze the strength and failure modes for the multi holes pin joint configurations made from unidirectional glass/epoxy nanoclay laminates. The geometric parameters, i.e. the distance from the free edge of the specimen to the diameter of the first two holes (E/D) ratio, the distance between two holes along the length of the specimen to the diameter of the hole (F/D) ratio, the distance between the two holes along the width of the specimen to the diameter of the hole (P/D) ratio and side width to diameter (S/D) ratio were studied for their effect on strength and failure modes of the joint. Design of experiment with Taguchi method was used for the optimization of different geometric parameters. Analysis of variance was applied to determine the influence of individual geometric parameter on the strength of the joint. The results demonstrate that the E/D and F/D ratios are the most significant parameters to increase the strength of multi holes pin joint configurations. Their percentage contributions were about 62% to 65% and 23% to 26%, respectively. Thereafter, the characteristic curve method along with Tsai–Wu failure criteria was applied to compare the numerical and experimental predictions.